The construction project manager in South Africa: analysis of industry-specific knowledge - Burger, Michelle; Venter, Basie; Zulch, Benita (University of the Free State, 2015)
Construction project managers in the built environment come from various backgrounds and knowledge bases; therefore, the project managers’ project management set may differ. The type of knowledge required to improve CPD training of project managers thus needs to be determined. This would raise the knowledge levels needed for built environment project managers. The aim of this article is to determine the knowledge needed for the successful management of projects within the built environment. Industry-specific guidelines for construction project management (PMBOK and SACPCMP) were obtained and analysed. Expert interviews were conducted with experienced specialists (n=10) who held a senior managerial position within project management in the built environment. A case study and email questionnaires (n=40) were also analysed to determine the type of knowledge required. Data analysis was done using Microsoft Excel 2003®. Three areas of knowledge were identified, namely project management knowledge, industry-specific knowledge and knowledge through experience. Of these, industry-specific knowledge was considered the most important, although all three were very important. Project management knowledge areas essential to project managers included the nine PMBOK knowledge areas from the PMI PMBOK guide, 4th edition 2008, four additional PMI Construction extension to the PMBOK areas, experience as well as built environment-specific knowledge. This study was limited to the nine knowledge areas and did not include stakeholder management as the tenth area. The results from all three test methods (interviews, questionnaires and a case study) indicated that knowledge was essential for effective leadership, trust and communication within a project. Without knowledge, these organisational factors were compromised and project success could be negatively affected. It is concluded that the knowledge needed for the management of projects within the built environment had to include industry-specific knowledge pertinent to the built environment. The knowledge required does not currently appear in a single document, and it is recommended that a new document or set of required skills be established.

mag projekbestuurders se kennisstel verskil. Die tipe kennis wat benodig word om VPO-opleiding van projekbestuurders te verbeter, moet bepaal word. Dit sal die kennisvlakke wat bou-omgewing projekbestuurders benodig, verhoog. Die doel met die artikel is om die benodigde kennisvlakke van ‘n projekbestuurder in die bou-omgewing vas te stel. Industriespesifieke konstruksieprojekbestuurriglyne (PMBOK en SACPCMP) is verkry en geanaliseer. Spesialis onderhoude is met ervare spesialiste (n=10) wat ‘n senior posisie in die bou-omgewing beklee, gehou. ‘n Gevallestudie en epos vraelyste (n=40) is ook ontleed om die tipe kennis wat benodig word te bepaal. Data-analise is gedoen deur Microsoft Excell 2003® te gebruik. Die drie kennisareas is projekbestuurkennis, industrie-spesifieke kennis en kennis deur ondervinding. Van die drie areas, is industrie kennis as die belangrikste gereken, alhoewel almal belangrik was. Projekbestuur kennisareas wat belangrik is vir projekbestuurders sluit die nege PMBOK kennisareas van die PMI PMBOK 4de uitgawe 2008 in, en vier addisionele areas van die PMI Konstruksie uitbreiding tot die PMBOK, kennis deur ondervinding en industrie-spesifieke kennis in. Die studie was beperk tot die nege kennis areas en het nie belanghebbendesbestuur as tiende area ingesluit nie. Die resultate van al drie toetsmetodes (onderhoude, vraelyste en ‘n gevallestudie) wys op die belangrikheid van kennis vir leierskap, vertroue en kommunikasie tydens ‘n projek. Sonder kennis word hierdie organisasiefaktore benadeel en kan projeksukses negatief beïnvloed word. Dit is bevind dat die kennis wat ‘n projekbestuurder in die bou-omgewing benodig industrie-spesifiek binne die bou-omgewing moet wees. Daar bestaan nie tans een dokument wat die totale kennisstel bevat nie. Dit word aanbeveel dat ‘n nuwe dokument of stel van vereiste kennis/vaardighede saamgestel word.
Keywords: Construction project management; Built environment; Industry knowledge; Project management knowledge; Experience